Western Sahara: the stalemate of the issue and the continuation of the state of no war and no peace - Biskri, Mounir; Guettas, Samir (Technium Social Sciences Journal, 2022)
This article attempts to provide insight into the long-standing subject of Western Sahara through analysis and criticism. In comparison, all international and regional efforts failed to resolve this situation. That has remained constant since 1975. As a result, this paper will explore the magnitude of this issue, its roots, and the reasons for its decades-long stagnation. On this premise, we have split the subject into four essential elements, which are as follows: The Western Sahara issue is a zero-sum strategy game between the conflicting parties. The involvement of major powers in the issue’s impasse will then focus on the United States of America, France, and Russia as new regional actors. Then we try to concentrate on the Guerguerat crisis as a new station for the Western Sahara issue’s stalemate. Finally, we will attempt to discuss the deadlock of this issue within the framework of the United Nations, which has likewise failed to find a solution. TRANSLATE with x <input id="LanguageMenu_svid" style="display: none;" autocomplete="on" name="LanguageMenu_svid" type="text" value="en"> <input id="LanguageMenu_textid" style="display: none;" autocomplete="on" name="LanguageMenu_textid" type="text"> English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian TRANSLATE with COPY THE URL BELOW <input id="ShareTextbox" name="ShareTextbox" readonly="readonly" type="text"> <!–a id="TwitterLink" title="Share on Twitter"> <a– id="FacebookLink" title="Share on Facebook"> </a–> Back <input id="EmailSubject" name="EmailSubject" type="hidden" value="Check out this page in 0 translated from 1"> <input id="EmailBody" name="EmailBody" type="hidden" value="Translated: 0%0d%0aOriginal: 1%0d%0a%0d%0aAutomatic translation powered by Microsoft® Translator%0d%0ahttp://www.bing.com/translator?ref=MSTWidget"> <input id="ShareHelpText" type="hidden" value="This link allows visitors to launch this page and automatically translate it to 0."> EMBED THE SNIPPET BELOW IN YOUR SITE <input id="EmbedSnippetTextBox" name="EmbedSnippetTextBox" readonly="readonly" type="text" value=" "> Enable collaborative features and customize widget: Bing Webmaster Portal Back